ANALYSIS OF FACTORS AFFECTING SOYBEAN IMPORTS IN INDONESIA - Fadlul Ulfa Pratiwi; A Faroby Falatehan; Tanti Novianti (RADJA PUBLIKA, 2024)
The purpose of the study is to determine how much soybean imports contribute to the total imports of the food crop subsector and the effect of production, harvest area, exchange rate and consumption on Indonesia's soybean imports. The data used in this study are secondary data in the form of time series data for the period 2002-2022 derived from surveys that have been processed by the Central Bureau of Statistics. The analysis method used is descriptive and quantitative analysis using simultaneous analysis tools. The results showed that the contribution of soybean imports to the total imports of the food crop subsector in Indonesia experienced a fluctuating increase each year with an average of 24.87 percent. Based on the results of multiple linear analysis, it is concluded that the factors influencing soybean imports in Indonesia are jointly influenced by the variables of soybean production, harvest area, exchange rate and Indonesian soybean consumption. While simultaneously and partially the variables of soybean production and consumption have a positive and significant influence on Indonesian soybean imports, while the variable of harvest area has a negative and significant effect, the exchange rate has a negative and insignificant effect on Indonesian soybean imports.